Thai EFL Students’ Ability to Reason as Results of Training in Written Argumentation - Kaewneam, Chamnong (LEARN Journal: Language Education and Acquisition Research Network, 2025)
Written argumentation involves providing reasons to support the writer’s stance on a contentious issue. A question arose in the study regarding how training in written argumentation would impact Thai EFL learners’ ability to reason. The research adopted a quasi-experimental design. A group of English for Communication students received training in writing argumentation, guided by an updated set of criteria for written argumentation: relevance, reasoning, organization, language use, and the writer’s voice (Kaewpet, 2018). Three sets of argumentative essays were collected from 38 students, providing data from before, during, and after the training. The essays were evaluated by three assessors using the same criteria. Differences in the students’ abilities were measured using ANOVA, followed by Tukey’s HSD (beta). Patterns of differences were also examined. The influence of argumentation and writing elements on the overall quality of the essays were assessed using Pearson correlations. The results revealed that students’ ability to reason differed significantly between the pre-training and post-training stages, with 39.47% of the students showing improved scores after the training. Both the ability to argue and the ability to write had a positive influence on the overall quality of argumentation written by students of all ability levels. The quality of most argumentation elements was rated as moderate. These elements had varying influences on the overall quality, ranging from weak to moderate to strong. The present study confirms the effectiveness of explicit training in written argumentation for enhancing English learners’ reasoning abilities and suggests the need for further investigation into students’ ability to engage in real-world situations that require critical thinking skills and intellectual capacity.